Subak dalam Perspektif Keteknikan - Haryono Haryono (INFO-TEKNIK, 2007)
Subak is organization with aim to to arrange irrigating as well as possible. There is three target which wish to be reached is prosperity of economics of the member, pacification of mind and also management of going concern water and with vision of environment. Target of this research is to determine factor of SWOT of execution of subak as one of the rural irrigating organization which have good enough pattern as one of [the] organizational alternative of P3A in in perpective isn't it. Strength of subak determined by tying bounce very strong for official member and religion public spirited member. Activity of agribisnis is good enough opportunity, if subak can exploit the opportunity. Weakness of organization of subak is activity of processing of marketing and result so that opportunity of effort the agribisnis more exploit by entrepreneur of more private sector of professional.